THE RELATIONSHIP BETWEEN PARENTING PATTERN AND STUDENT LEARNING ACHIEVEMENT IN PERGETTENG GETTENG SENGKUT VOCATIONAL SCHOOL (PGGS) - Mustaruddin; Beta Hanindiya (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2022)
Parenting is the way or attitude of parents in influencing and educating their children to behave in a healthy life. The forms of parenting applied by parents are democratic, authoritarian, and permissive parenting. Learning achievement is the average score of students' final semester exam results. The research objective was to identify the relationship between parenting parents and student achievement at SMK PGGS Salak This study uses a correlation descriptive research design. The population in this study were students of Pergetteng-getteng Sengkut Vocational School (PGGS) Salak, Pakpak Bharat Regency, class XI, namely 100 people. The number of samples obtained based on calculations was 50 students. The sampling technique used a simple random sampling approach. This research instrument consists of 3 types of student demographic data questionnaires, Parenting Patterns and Learning Achievement. To assess the strength of the relationship between parenting style and academic achievement, the Pearson correlation test was used. The results showed that 31 respondents (62%) were categorized as good parenting styles, and almost all respondents were in the moderate learning achievement category, namely 43 respondents (86%). Parenting style has a positive and adequate relationship with student achievement, with a significant value obtained of 0.000 (p=0.05), so that it can be concluded that there is a relationship between parenting styles and student achievement at Pergetteng-getteng Sengkut Vocational School (PGGS) Salak, Pakpak Bharat Regency. The research results obtained can be used as basic data and information for further research and it is recommended to pay more attention to data collection methods so that the data obtained is more accurate and representative